KEANEKARAGAMAN JENIS SATWALIAR DI KAWASAN PERKEBUNAN KELAPA SAWIT DAN STATUS PERLINDUNGANNYA DI AREAL ESTATE SUNGAI TERIK PT. NUSA LESTARI, SERUYAN PASER KALIMANTAN TIMUR - Harnios Arief (Department of Forest Resources Conservation and Ecotourism - IPB University, 2013)
Regions Oil Palm Estate Management Unit Sungai Terik, Nusa Lestari Ltd is largely secondary forest. Land cover conditions have degraded because of existing timber companies operating in this region from 1990. The inventory and identification of wildlife species diversity in the plantation done to be able to know the types that still exist in this area of oil palm companies. From the observation found 32 species of mammals which belong to 14 families, 170 species of birds belonging to the 42 families and 9 species of reptiles. Local protected areas that border the river is one important area for the protection and preservation of endangered species / protected. This condition is caused because it can be found 20 species of mammals, 41 species of birds and one reptile species endangered / protected in the region. Keywords: ecosystem, habitat, wildlife, and wildlife species diversity.